ANALISIS PUTUSAN PENGADIKAN AGAMA PEKANBARU NOMOR 2189/pdt.g./2022/PA.pbr. TENTANG HAK ASUH ANAK YANG BELUM MUMAYYIZ - Rinaldi, Hendri (Khulasah : Islamic Studies Journal, 2025)
This research was motivated by the decision of the Pekanbaru Religious Court judge regarding the custody of children who have not yet been mumayyiz by their father in Article 105 a jo Article 156 KHI which shows that there is a discrepancy with the compilation of Islamic law. Apart from that, the decision of the Pekanbaru Religious Court judge is also influenced by the legal sources used and considering the benefit of the child. Therefore, this research focuses on analyzing the PA decision Number 2189/Pdt.G/2022/PA.Pbr regarding custody of children who are not yet mumayyiz, the fundamental objective of this research is to analyze the PA decision Number 2189/Pdt.G /2022/PA.Pbr regarding custody of children who are not yet mumayyiz, where the method used in this research is qualitative in the form of normative juridical research, in this case namely the Compilation of Islamic Law, the data collection method is through literature study, while the data analysis technique is through study analysis, presenting it as a fact that can be drawn as a conclusion. From the results of the research conducted by the author, it can be concluded that religious court judges in deciding a case are not only based on the applicable formal law. In this case, a young child still does not know what is good for him, the child still needs the presence of other people to help handle his affairs and provide care for him, namely by bestowing goodness and preventing him from dangers, the panel of judges in deciding decision Number 2189/Pdt.G/2022/PA.Pbr is in the interests of the child himself, because the child has a closer emotional relationship with the father, and the father has the ability and ability to care for the child, so in this case the father He is indeed more entitled to receive custody.